Acupuncture injection for field amplified sample stacking and glass microchip‐based capillary gel electrophoresis. Issue 3 (20th December 2016) - Ha, Ji Won; Hahn, Jong Hoon
Abstract : Acupuncture sample injection is a simple method to deliver well‐defined nanoliter‐scale sample plugs in PDMS microfluidic channels. This acupuncture injection method in microchip CE has several advantages, including minimization of sample consumption, the capability of serial injections of different sample solutions into the same microchannel, and the capability of injecting sample plugs into any desired position of a microchannel. Herein, we demonstrate that the simple and cost‐effective acupuncture sample injection method can be used for PDMS microchip‐based field amplified sample stacking in the most simplified straight channel by applying a single potential. We achieved the increase in electropherogram signals for the case of sample stacking. Furthermore, we present that microchip CGE of ΦX174 DNA‐HaeⅢ digest can be performed with the acupuncture injection method on a glass microchip while minimizing sample loss and voltage control hardware.